Identification and Minimization of Waste with the Application of Lean Manufacturing in the Cireng Production Process at PT Brecxelle Berkah Uniti - Firizky Tania Dwi Wanda,; Santika Sari, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Based on the results of observations and the 7 waste questionnaires at PT Brecxelle Berkah Uniti production, it was found that the waste of defects occurs such as cireng are shapeless, destroyed, and do not pass through the metal detector machine. Waste of waiting occurs during the cooling process, when starting the engine, and waiting for the pressing process. Waste of transportation occurs due to circular and non-consecutive process flows. This research aims to minimize production time and increase production result by simulating the cireng production process of PT Brecxelle Berkah Uniti using the Lean Manufacturing and System Simulation method. Based on the simulation results with the proposed improvements, the results obtained from the simulation were that the total production lead time was reduced by 10,97 minutes from 40.45 minutes to 29,48 minutes. The NVA and NNVA time on FVSM also decreased by 10.81 minutes from the activity time on CVSM. Based on the simulation results, production results increased by 80% after the proposed improvements, from 4,671,945 pcs per month to 8.429.679 pcs per month.